The enrichment influences of Artemia urmiana with vitamin E and unsaturated fatty acids on growth, survival and salinity stress resistance in beluga (Huso huso) larvae - Jalali, M.A.; Hosseini, S.A.; Imanpour, M.R.; Alimohammadi, A.A. (2008)
VWe assessed the effects of Aremia urmiana nauplii enriched with vitamin E (α -tochopherol acetate, MERCK, Germany) and unsaturated fatty acids (EPA 18% and DHA 12%) on growth, survival and stress resistance of Beluga (Huso huso) larvae during six weeks. Beluga larvae (mean body weight 69.8c6.2 mg) at the first feeding were fed in four treatments and three replications using A. urmiana enriched with unsaturated fatty acids (HUFA) containing 20% and 50% vitamin E (El and E2 treatments, respectively) and HUFA without vitamin E (HUFA group). The control group was fed on non-enriched Artemia. All treatments were fed with non-enriched Artemia for 5 days after the first feeding and then fed with enriched Artemia for 7 days. After period of enrichment, the larvae were fed with daphnia from 13 ^(th) to 40 ^(th) day. The Beluga larvae were then exposed to salinity stress (12 g/l) for two days after the 40 days feeding trial. Blood samples were obtained at the end of the first and second days in order to evaluate hematocrite index. Growth, survival and stress resistance were compared at the end of experimental period. Growth factors showed significant difference between the groups. The highest and the lowest growth were observed in El and control treatments, respectively (P<0.05). Larvae resistance to salinity stress was comparable between the enriched and control groups (P< 0.05). The results indicated that the enrichment of Artemia with essential fatty acids and vitamin E can improve some growth and stress tolerance factors in beluga sturgeon (H. huso) larvae.